Selenium supplementation enhances weight gain in cattle - Reis, L. S L S (2008)
To evaluate the effect of selenium on cattle growth in a continuous grazed pasture system. Selenium was added to protein-mineral salt and given to male, around-12-month old, non-castrated Nellore calves. Animals were randomly and equally distributed into 4 groups (15 calves/group) which received supplementation containing 0, 3.6, 5.4 or 6.4 mg selenium/animal/day (groups Gc, G 3.6, G 5.4 and G 6.4, respectively). The animals were weighed on day zero and 120, and the pasture forages were collected at day 0 for chemical analyses. Weight gain was higher in cattle from G 5,4 (45.58%) than in the other groups, and higher in G 3,6 (24.97%) and G 6,4 (22.67%) than in Gc. The supplementation with 5.4 mg selenium/animal/day enhanced weight gain in cattle fed on selenium poor diet (0.04 mg Se/kg dry matter).